Haplotype analysis encompassing HTT gene in Chinese patients with Huntington's disease. (17th October 2019) - Li, X.‐Y.; Li, H.‐L.; Dong, Y.; Gao, B.; Cheng, H.‐R.; Ni, W.; Gan, S.‐R.; Liu, Z.‐J.; Burgunder, J.‐M.; Wu, Z.‐Y.
Abstract : Background and purpose: Huntington's disease (HD) is a dominantly inherited neurodegenerative disorder with varied prevalence in different populations, which may be associated with specific haplotypes. This study aimed to explore the haplotypes encompassing the HTT gene in the Chinese population. Methods: A total of 406 individuals with HD and 59 normal relatives from 253 families with HD were enrolled. A total of 29 tag single nucleotide polymorphisms (tSNPs) were selected and genotyped for the haplotype analysis. Results: In stage one, we used 18 tSNPs to replicate the distribution of three major haplogroups (A, B, C). We found that risk‐associated haplogroup variants A1 and A2, enriched on Caucasian HD chromosomes, were totally absent from both Chinese HD and control chromosomes, and the distributions of haplogroups between HD and control chromosomes were similar. Therefore, in stage two, we used 29 tSNPs (including the18 tSNPs) to define new haplogroups (I, II, III) and found that haplogroup I accounted for 61.4% on HD chromosomes and 34.4% on control chromosomes, indicating that haplogroup I was enriched on Chinese HD chromosomes. Conclusions: This is the first haplotype analysis encompassing HTT in the Chinese population. The results contribute to explaining the low prevalence of HD in China and provide a better understanding of genetic diversity in the HTT region.